Coaching empreendedor: estudo sobre sua influência no incremento das competências e no desempenho de empreendedores - Pinto, Neusa Maria Lopes (2012)
This study aimed to bring more light to the concept of coaching, as well as verify how much this process can facilitate the development of young entrepreneurs’ competences. In order to achieve this objective, the study’s foundation was the constructivist theories of learning, which are the basis of the coaching way of thinking. For being aninherently reflexive process, it was chosen to introduce projective exercises which could give something concrete for analyzing the young entrepreneurs’ development in the competences they value. It also contributed for raising the alternatives used by them for their improvement. The field research involved 10 (ten) young entrepreneurs associated to 2 (two) incubators (in the states of São Paulo and Rio de Janeiro) and the interviews were led following a questionnaire/roadmap, aiming to risetheir own perceptions regarding their own development in the competences they considered important. Based on the quality of the choices and decisions expressed by the young entrepreneurs, analyzed through Bardin’s (1977) content, it was possible to infer the entrepreneurs’ state of change (E.E.M.). Conclusions were possible since the researcher has worked with traces, state manifestations, data and phenomena, which allowed the deduction, in a logical way, of the message sender’s knowledge (BARDIN, 1977). It was possible to observe that young entrepreneurs, who, most of the time, have a high technical competence, search for developing their managerial and social competences, motivated to create and maintain their independence in thoughts and actions. It was concluded that coaching can be understood as a process that facilitates and accelerates the incrementof those competences in order to ensure that the goals established by the entrepreneurs themselves will be achieved.